Analysis‐suitable CAD Models based on Watertight Boolean Operations. Issue 1 (9th September 2019) - Marussig, Benjamin; Urick, Benjamin; Cohen, Elaine; Crawford, Richard H.; Hughes, Thomas J. R.; Riesenfeld, Richard F.
Abstract: Isogeometric analysis has established a new paradigm in computational engineering that significantly improves the interoperability problem between design and analysis, but addressing the full scope of the issue requires adaptations of traditional CAD concepts as well. The recently introduced watertight Boolean operations resolve a fundamental inconsistency in the underlying representations of current CAD models. We investigate the suitability of the resulting geometries for analysis purposes; in particular, in the context of isogeometric boundary element methods. The results confirm that watertight Boolean operations yield CAD models that meet the requirements of numerical simulations.